Utilization of locally available organic matter to improve chemical properties of pyroclastic materials from Mt. Kelud of East Java - S R Utami; C Agustina; K S Wicaksono; B D Prasojo; H Hanifa (Journal of Degraded and Mining Lands Management, 2017)
Pandansari village, Ngantang District was severely affected by Mt. Kelud eruption in 2014. Almost all soil surfaces were covered by the eruption product, leading to serious problems for cultivation. Pyroclastic materials potentially have high content of nutrients, but they are not readily available to plants. As an attempt to improve chemical properties of the pyroclastic materials, we applied locally available organic matters, from four different sources, i.e. leaves of sweet potatoes, Tithonia diversifolia, maize, and cow manure. The pyroclastic materials were sieved at 2 mm, placed inside pots (50 x 50 x 50 cm3), until it reached 30 cm thick. The fresh leaves were chopped into 2 mm size and mixed with the pyroclastic materials at the dosage of 15 Mg/ha. They were incubated and kept at field condition. Selected chemical properties (pH, CEC, sum of basic cations, and the total contents of N, organic C, and available P) were measured before and after 90 days incubation. The results showed that after 90 days, organic matter application significantly increased pH, cation exchange capacity, organic C, and total exchangeable basic cations content. The increases of P-available and total N contents were only detected on cow manure treated materials.